2019
DOI: 10.3390/s19071568
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection in Wireless Sensor Networks through the Random Forest Classifier

Abstract: Wireless Sensor Networks (WSNs) are vulnerable to faults because of their deployment in unpredictable and hazardous environments. This makes WSN prone to failures such as software, hardware, and communication failures. Due to the sensor’s limited resources and diverse deployment fields, fault detection in WSNs has become a daunting task. To solve this problem, Support Vector Machine (SVM), Convolutional Neural Network (CNN), Stochastic Gradient Descent (SGD), Multilayer Perceptron (MLP), Random Forest (RF), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 34 publications
1
54
0
6
Order By: Relevance
“…To evaluate the performance of the CNN-RF method, other traditional methods were selected for a comparison of prediction accuracy. The selected methods were KNN [11], ELM [15], SVM [17], LVQ [18], [19], BP [20], RF [39], and CNN-RF, the last of which (i.e., the proposed model) had higher accuracy than the other methods under noisy environment. The comparison results, in terms of sensor fault diagnosis accuracy, are shown in Table 5.…”
Section: ) Cnn-rf Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the performance of the CNN-RF method, other traditional methods were selected for a comparison of prediction accuracy. The selected methods were KNN [11], ELM [15], SVM [17], LVQ [18], [19], BP [20], RF [39], and CNN-RF, the last of which (i.e., the proposed model) had higher accuracy than the other methods under noisy environment. The comparison results, in terms of sensor fault diagnosis accuracy, are shown in Table 5.…”
Section: ) Cnn-rf Inferencementioning
confidence: 99%
“…Therefore, it is more suitable to use RF when respect to a large number of data with reasonable features, especially under noisy environment. The literature [38], [39] has demonstrated that sensors fault diagnosis based on RF is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…RF is intended to achieve an optimized, supervised and structured resolution for labelled problems, which is proven to given more accurate results compared to many other supervised machine learning algorithms. In [9], RF is compared to numerous classifiers of different functionalities for its ability to overcome two occurring sensor faults in Wireless Sensor Networks (WSNs), which are spike fault and data loss fault. This study represents an elaborated comparison between RF, Support Vector Machine (SVM), Stochastic Gradient Descent (SGD), Multilayer Perceptron (MLP), Convolutional Neural Network (CNN) and Probabilistic Neural Network (PNN), using Detection Accuracy (DA), Matthews Correlation Coefficients (MCC), True Positive Rate (TPR) and F1-score as the comparison criteria that determine the overall rank of each method.…”
Section: Related Work: Rf For Fdd In Industry 40mentioning
confidence: 99%
“…Fault detection and diagnosis can improve the reliability of sensor networks and enhance its bandwidth of operation. There are various techniques as reported in recent research surveys related to fault detection and diagnosis in sensor networks [10][11][12][13]. Incidentally, it is worth noting that while choosing fault detection methods, care should be taken to reduce the energy consumption and ease of integration with the existing networks.…”
Section: Introductionmentioning
confidence: 99%
“…If MCC is of +0.7 or higher, it can be considered as excellent, from +0.4 to +0.69, it can categorized as good and from +0.30 to +0.39 it is moderate. When it reaches +0.20 to +0.29, it is considered as weak.The F1-Score[13] is used to measure the performance of the classifier based on false positive and false negative values. It is defined as follows.…”
mentioning
confidence: 99%